Reply to the discussion by Dimitrios Kolymbas of the article entitled “Characteristic limitations of advanced plasticity and hypoplasticity models for cyclic loading of sands” (2023)
The authors welcome the note provided by Prof. Kolymbas regarding his analysis of the characteristic limitations using the Barodesy model. It is very enriching to let users know about the performance of some other constitutive models around the characteristic limitations shown by the authors. Self-criticism of own constitutive developments and letting the users be aware of each model’s advantages and limitations demonstrates the seriousness of each work and is essential for future improvements. In the following, the authors present some comments and thoughts regarding the simulations with the Barodesy model